Nigeria : Methodological Approach for Development of a Target Deposit Insurance Fund Model - World Bank Group (World Bank, Washington, DC, 2016)
Principle 11 of the International Association of Deposit Insurers (IADI) Core Principles (CP 11) states that deposit insurers are required to have available to them all funding mechanisms necessary to ensure the prompt reimbursement of depositors’ claims. One of the Essential Criteria under CP 11 is that the size of the fund, the “fund reserve ratio”, should be based on “clear, consistent and well-developed criteria.” Currently, the Nigerian Deposit Insurance Corporation (NDIC) sets its reserve ratio based on a formula that may not properly consider future risks as it is based partially on the level of insured deposits in banks deemed to be in distress.